The letters of Robert Grosseteste, Bishop of Lincoln - Grosseteste, Robert, 1175?-1253.; Mantello, Frank Anthony Carl, 1945-; Goering, Joseph Ward, 1947- (Toronto [Ont.] : University of Toronto Press, 2010)
This volume contains the first complete translation of Grosseteste's collected Latin letters and shows that these were most likely chosen and arranged by Grosseteste himself. Shedding light on some of the period's crucial debates on issues of theology, law, pastoral care, and episcopal authority, Frank Mantello and Joseph Goering's richly annotated English translation makes his letters more accessible than ever for scholars and students, and for those interested in medieval history, religion, and culture"--Bk. jacket.
101. To Henry III, king of England -- 102. To Henry III, king of England -- 103. To Eleanor, queen of England -- 104. To Otto of Tonengo, cardinal deacon and papal legate in England -- 105. To Otto of Tonengo, cardinal deacon and papal legate in England -- 106. To Martin, papal chamberlain, nuncio, and collector of revenues -- 107. To the archdeacons of the diocese of Lincoln -- 108. To the abbot and monks of Fleury -- 109. To the abbot and monks of Citeaux -- 110. To Otto of Tonengo, cardinal deacon and papal legate in England -- 111. To Pope Innocent IV -- 112. To the archdeacons of the diocese of Lincoln -- 113. To William of Raleigh, bishop of Winchester, and Walter of Cantilupe, bishop of Worcester -- 114. To William of Nottingham, Franciscan provincial minister -- 115. To Hugh of St Cher, cardinal priest of Santa Sabina -- 116. To Walter de Gray, archbishop of York -- 117. To Pope Innocent IV -- 118. To 'T., ' appointee to a pastoral charge -- 119. To Henry III, king of England -- 120. To John of Offington, papal chaplain -- 121. To the dean and chapter of Lincoln Cathedral -- 122. To the dean and chapter of Lincoln Cathedral -- 123. To the regent masters in theology at Oxford -- 124. To Henry III, king of England -- 125. To Henry III, king of England -- 126. To Boniface of Savoy, archbishop of Canterbury -- 127. Document setting out Grosseteste's position on visitation of the dean and chapter of Lincoln Cathedral -- Appendix A. The Chapter's Objections to Episcopal Visitation -- Appendix B. Letter (25 August 1245) of Pope Innocent IV concluding the Disputebetween Bishop Grosseteste and His Chapter -- 128. To Stephen de Montival, archdeancon of Canterbury, and Innocenzo, papal scriptor -- 129. To Robert Marsh, Grosseteste's official -- 130. To the regular and secular clergy of the diocese of Lincoln -- 131. To the lords of England, citizens of London, and common people of the realm -- 132. To the archdeacons of the diocese of Lincoln -- Appendix: Summaries of Letters, by Correspondent.
Translated from the Latin.
Includes bibliographical references (p. [485]-489) and indexes.
Keywords: Grosseteste, Robert, -- 1175?-1253 -- Correspondence; Catholic Church -- Great Britain -- Bishops -- Correspondence; Philosophers -- Great Britain -- Correspondence; Philosophers, Medieval -- Correspondence; Theologians -- Great Britain -- Correspondence; HISTORY / Europe / Great Britain; PHILOSOPHY / History & Surveys / Medieval; Electronic books